2018
DOI: 10.1159/000489305
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and Wheat Allergy: A Growing Association?

Abstract: Introduction: Celiac disease and wheat allergy (WA) are infrequent diseases in the general population, and a combination of the 2 is particularly rare. Celiac disease occurs in around 1% of the general population and WA in around 1% of all children. Case Report: We report 2 patients with celiac disease and a gluten-free diet who developed WA consistent in anaphylaxis and an eyelid angioedema, respectively, through accidental wheat exposure. A serum study and an intestinal biopsy confirmed celiac disease. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 9 publications
(13 reference statements)
2
13
0
Order By: Relevance
“…Patients with coeliac disease also have the possibility to also develop wheat allergy. Micozzi et al presented two cases of children with coeliac disease who subsequently had allergic reactions to wheat due, it is proposed, by sensitization to the trace amounts of wheat in gluten-free foods (82). Another group from Spain also published case reports of two children with coeliac disease who developed allergic reactions immediately after accidental exposure to wheat, with the wheat allergen Tri a 14 (wheat LTP) the responsible allergen (83).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with coeliac disease also have the possibility to also develop wheat allergy. Micozzi et al presented two cases of children with coeliac disease who subsequently had allergic reactions to wheat due, it is proposed, by sensitization to the trace amounts of wheat in gluten-free foods (82). Another group from Spain also published case reports of two children with coeliac disease who developed allergic reactions immediately after accidental exposure to wheat, with the wheat allergen Tri a 14 (wheat LTP) the responsible allergen (83).…”
Section: Resultsmentioning
confidence: 99%
“…Micozzi et al [13] suggested 3 possible explanations for WS in patients on a GFD. First, WS could be masked by symptoms of CD, so gastrointestinal symptoms could be due to WA and not just CD.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Other studies evaluating sensitization to wheat and/or rye, barley, and malt in CD patients did so as case reports (n = 9) [9][10][11][12][13][14][15]. Anaphylaxis episodes have been reported in 3 patients [12,14,15], 1 of whom died [12].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations